Cultural Influences on Body Image: A Thematic Analysis of Social Media Perception Among Young Pakistani Women - Nisa, Ulfat; Ahmed, Aqeel; Elahi, Haroon (Journal of Peace, Development and Communication, 2024)
Stereotyped body image has been among the many perceptions cultivated by the exposure to various social media platforms. The dearth of qualitative research in general and Pakistani context in particular prompted researchers to explore how individuals perceive their bodies, under cultural influences, in context of social media use. The current focus group discussion involved ten Islamabad-based university going women aged 18-25 through convenience purposive sampling and carried out a thematic analysis under the guidelines from thematic analysis method as proposed by Braun and Clarke (2006). The themes explored; Sociocultural Body Ideals, Social Media Body Perceptions, Social Circle Impact, and Sociocultural Norms and Expectations, reflected upward and downward social comparisons as well as sociocultural influences. By providing valuable insights into sociocultural context, social media usage by young Pakistani women and their consequent perception about body image, this study paves way for future researchers to explore psychological implications of the negative body image perception.